THE INTEGRATED CURRICULUM AS A STRATEGY TO OVERCOME CURRICULUM FRAGMENTATION IN FULL-TIME SCHOOLS - Silva, Jardelson de Medeiros (Seven Editora, 2026)
This article analyzes the integrated curriculum as a strategy to address curricular fragmentation in full-time schools, considering its theoretical, historical, and normative foundations. It begins with the recognition that the traditional disciplinary organization of the curriculum has limited holistic human development, even in contexts of extended school hours. The research is characterized as a qualitative study, with a theoretical-documentary approach, based on the analysis of academic productions in the field of curriculum and normative documents of Brazilian education. The results show that the extension of school hours, when not accompanied by an integrated curricular reorganization, tends to reproduce the dichotomy between curricular and complementary activities, weakening the project of comprehensive education. The discussion points out that the integrated curriculum is configured as a political-pedagogical principle capable of articulating knowledge, times, spaces, and educational practices, favoring meaningful, contextualized learning committed to social justice. It is concluded that the implementation of an integrated curriculum requires not only normative guidelines, but also institutional conditions, coordinating school management, and collective processes of curriculum construction, reaffirming comprehensive full-time education as an educational project aimed at the complete human development.